Case Report: Eculizumab and ECMO Rescue Therapy of Severe ARDS in Goodpasture Syndrome - Sobotta, Michael; Moerer, Onnen; Gross, Oliver (Frontiers in Medicine, 2021)
Introduction: Goodpasture’s syndrome is a life-threatening autoimmune type IV collagen disease characterized by the presence anti–glomerular basement membrane antibodies, rapid progressive glomerulonephritis and/or pulmonary hemorrhage. Methods: Here, we describe new therapeutic options, which take recent advances in unraveling Goodpasture’s pathogenesis into account. Results: In a 17-year old male smoker, severe Goodpasture’s syndrome resulted in acute respiratory distress syndrome (ARDS). Within one day after hospital admission, the patient required extracorporeal membrane oxygenation (ECMO). Despite steroid-pulse and plasmapheresis, ARDS further deteriorated. Eleven days after admission, the patient was in a pre-final stage. At last, we decided to block the complement-driven lung damage by Eculizumab. Three days after, lung-failure has stabilized in a way allowing us to initiate Cyclophosphamide-therapy. As mechanical ventilation further triggers Goodpasture-epitope exposure, the patient was taken from pressure support - breathing spontaneously by the help of maintaining ECMO therapy. After a total of 24 days, ECMO could be stopped and pulmonary function further recovered. Conclusions: In conclusion, our findings suggest that life-threatening organ-damage in Goodpasture’s syndrome can be halted by Eculizumab as well as by lung-protective early withdrawal from pressure support by the help of ECMO. Both therapeutic options serve as new tools in otherwise hopeless situations to prevent further organ-damage and to gain time until the established immunosuppressive therapy works in otherwise letal autoimmune-diseases.